Franciszek Próchnicki – polonista na wczoraj i dziś - Gajak-Toczek, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
Franciszek Próchnicki belongs to the outstanding representatives of grammar school Polish studies during the last quarter of the XIX century. He was born in 1847 at Brzeżany. After graduation from the Lvow University he became a Polish secondary-school-teacher, at first at his home town and, later at Lwów. In this town he acted as a headmaster of the Secondary School No 5 from 1891 till to 1905, when he went retired. Próchnicki was known as the author of a number of instructions, programs and textbooks for Polish-language for Primary and Secondary Schools. All his life Próchnicki devoted to teacher’s occupation. He died at Lwów in 1911.